Effect Repetition of Anticyclone and on thermal characteristic in Iraq - بدر جدوع احمد سرى حسين محمد (College of Education for Women, 2019)
Anticyclone of synoptic studies that influence weather and climate of Iraq, The aim of the study is to clarify the effect variation of repetition of Anticyclone and effect on thermal characteristic in Iraq were pressure level has been analyzed (1000) millibars and that because of pressure level is the closet to the earth surface and the clarity of climatic phenomenon based on a systematic analysis of synoptic seeking maps and observation and (12:00) according to timing GMT for five climatic stations which is (Mosul, Kirkuk, Baghdad, Rutba, and Basra) and so far three consecutive climatic cycles which is first climatic cycle for period (1986-1976). and second climatic cycle for period (1997-1987) and third climatic cycle for period (2008-1998).It become clear from the result. That study reach, It become clear that a clear depression in repetition of Anticyclone from climatic session to another climatic session followed by three climatic session and on all level of study area stations. The contrast repetition of Anticyclone is one of the factors that help to raise the temperature due to air stillness and the clarity of the sky that led to the concentration of pollutant and slow in their transition to other areas. These pollutant increase rising temperatures air textures to the surface of earth because it absorb ground radiation at night and reflect it to surface of earth as well as the clarity of the sky during the day helped to increase the amount of solar radiation to the earth it is found rising temperatures Siberian is the station (Mosul, Kirkuk, Rutba) for October month for second climatic cycle for period (1997-1987) and third for period (2008-1998) as well as increase temperatures maximum rate with increasing repetition rate of high semi-orbital in the stations Mosul, Kirkuk, and Rutba area for each month of January and October in the second climatic session for period (1997- 19987) as well as in the third climatic cycle for period (2008-1998) in all stations of studying area for months of January and march and October and the high rate of maximum temperature with high rate repetition of European Anticyclone in all stations of studying area in the second climatic cycle for period(1997-1987) 0f January, march, October months, Notice increase repetition rate of Siberian Anticyclone in the month of October for two climatic cycle second and third as well as Basra station recorded increase in minimum temperature rate with increase repetition rate of high semi-orbital in the second climatic cycle for period (1997-1987) for January as well as in all stations of studying area in the third climatic cycle for period (2008-1998) for march also in stations of Mosul, Kirkuk, Basra for two climatic cycle the second and the third for October. And high rate of minimum temperature with high repetition rate of European Anticyclone in the stations of Kirkuk and Basra in January for the second climatic cycle period (1997-1987) as well as recorded in march month in stations of Mosul and Kirkuk, Basra for two climatic cycle the second and third also in October for the second climatic cycle for stations of studying area.